Theoretical bases of formation of readiness of future foreign language teachers to the monitoring activities - Рожелюк, Ірина Ярославівна (Pedagogy of Higher and Secondary Education, 2017)
The article is devoted to the research of theoretical bases of formation of readiness of future foreign language teachers to monitoring activities by means of psychological structure specifying their professional activities and concepts of monitoring in education. Current status of the foreign language teacher is represented by his/her role as an organizer and manager of foreign education, capable of monitoring the implementation of the quality features of the academic success of those studying a foreign language, as well as to identify the level of his/her pedagogical activity. It has been specified that the professional activity of the foreign language teacher should be understood as hierarchically organized system of different types of his/her functional responsibilities, aimed at seeking, receiving and systematizing scientific knowledge, constructing it in a scientific discipline, organizing and promoting scientific and cognitive activity of those who study a foreign language in order to master the knowledge, as well as to evaluate and monitor the quality of their foreign education and multicultural upbringing by measuring the levels of their academic success to create more favourable conditions for the development of language personality. The presence in the structure of the professional activity of the foreign language of a diagnostic and analytical assessing function indicates on a special component of the monitoring activities, which in the context of the key principles of quality management system of foreign education and educational practice of external independent testing acquires special significance. Given the major functions and ways of monitoring in education the author formed a definition of readiness of the future foreign language teachers to the monitoring activities. Readiness to monitoring activity refers to the ability of the future teacher of a foreign language to planning, implementation and generalization of the results of educational measurement by integrating relevant psycho-pedagogical and mathematical and statistical knowledge, practical skills and experience in the pedagogical management and monitoring of the system of foreign education, detection humanistic values and moral and ethical features during the evaluation of quality of the academic achievements of students who study a foreign language and culture. It has been proved that this is a dynamic and systematically structured neoplasm of the personality of the future foreign language teacher, whose structure consists of four major components: cognitive, active, motivational and personal.